PERAN RELIGIUSITAS DAN KEHALALAN PADA NIAT BELI KONSUMEN - Saktiana, Galuh Mira (Jurnal Manajemen, 2024)
The purpose of this study is to test the factors that affect high consumer purchasing intentions is due to a positive attitude in the product. Factors that can influence a consumer being positive on Korean halal noodle products are the level of religiosity, halal logo, halal awareness, halal certification, and safety ingredients. This study uses a non -probability method with the purposive sampling method, the sample size is 231 respondents and the analysis test using Sem Amos 22. The results of this study are religiosity, halal logo, halal awareness, halal certification and halal security positive and significantly on attitudes. Then the attitude as a provision of the relationship between religiosity in consumer purchasing intentions is proven.